Advances on the Use of Graphene as a Label for Electrochemical Biosensors. Issue 20 (21st July 2020) - Bonanni, Alessandra
Abstract: There has been an overwhelming interest in the use of graphene and its derivatives for electrochemical biosensors in the last decade. Although the majority of the works describe the use of these materials as platform for the immobilization of the biorecognition element, there is a significant, often unrecognized, research effort that has shown how graphene materials can also beneficially serve as signaling labels for biosensing. Owing to its intrinsic electroactivity and small size, nano‐graphene oxide, for example, has been used for this purpose, where the working signal arises from the reduction of the oxygen functionalities on the material surface. In other approaches, graphene labels modified with electroactive probes were also used to promote the signal generation. This Minireview will illustrate how the unique electrochemical and structural features make graphene a very promising material for the detection of the biorecognition event. In addition, an overview will be provided, showing the plethora of options offered by graphene and its derivatives as labels for signal generation and enhancement. Abstract : Graphene as label : An overview is provided in this Minireview, showing the plethora of options offered by graphene and its derivatives as labels for signal generation and enhancement in biosensing.